2016
DOI: 10.1021/acs.biochem.6b00645
|View full text |Cite
|
Sign up to set email alerts
|

A Variable Active Site Residue Influences the Kinetics of Response Regulator Phosphorylation and Dephosphorylation

Abstract: Two-component regulatory systems, minimally composed of a sensor kinase and a response regulator protein, are common mediators of signal transduction in microorganisms. All response regulators contain a receiver domain with conserved active site residues that catalyze the signal activating and deactivating phosphorylation and dephosphorylation reactions. We explored the impact of variable active site position T+1 (one residue C-terminal to the conserved Thr/Ser) on reaction kinetics and signaling fidelity, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 82 publications
(237 reference statements)
1
33
0
2
Order By: Relevance
“…Conspicuous examples of variable residues can be mapped to Thr 81(RR) , well positioned to interact with the phosphoryl group of P~DesK, or yet Phe 82(RR) and Arg 84(RR) , key players in the open/closure switch of DesR’s phosphate lid. Some of these positions had already been pinpointed as highly variable, yet functionally relevant (Thomas et al, 2013Immormino et al, 2016; Page et al, 2016), recognizing positions T + 1 and T + 2 (starting from T, the conserved position Thr 80(RR) ) among others, as important modulators of RRs’ catalytic activities. Particular sequence signatures of these variable motifs, have been found to correlate with RR families, in turn connected to the distinct physiological constraints of each family’s signaling functions (Page et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Conspicuous examples of variable residues can be mapped to Thr 81(RR) , well positioned to interact with the phosphoryl group of P~DesK, or yet Phe 82(RR) and Arg 84(RR) , key players in the open/closure switch of DesR’s phosphate lid. Some of these positions had already been pinpointed as highly variable, yet functionally relevant (Thomas et al, 2013Immormino et al, 2016; Page et al, 2016), recognizing positions T + 1 and T + 2 (starting from T, the conserved position Thr 80(RR) ) among others, as important modulators of RRs’ catalytic activities. Particular sequence signatures of these variable motifs, have been found to correlate with RR families, in turn connected to the distinct physiological constraints of each family’s signaling functions (Page et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We initially suggested that the missing phosphorylation signal of Agp2 could result from a rapid dephosphorylation by the response regulator. Dephosphorylation activity is described for diverse response regulators . Since no free phosphate was detected in our samples, however, we rejected the idea of rapid phosphate turnover.…”
Section: Discussionmentioning
confidence: 89%
“…A). Our initial interpretation of this observation was that the response regulator catalyses a rapid transphosphorylation and dephosphorylation and that ammonium sulphate would inhibit this turnover. We therefore mutagenized the Asp783 residue of the Agp2 response regulator and tested the mutants for phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…In order to exploit the information available from the high‐resolution structure of LqsR for functional insights, we engaged on a mutational analysis. Along with the LqsR D108E mutant, harboring a mutation in the phosphate acceptor aspartate like the previously studied LqsR D108N mutant (Schell et al, ), we targeted amino acid residues at positions in the receiver domain that, based on work with the CheY response regulator (Immormino et al, ; Page et al, ; Thomas et al, ), are likely involved in LqsR phosphorylation (G 135 , A 110 /Q 136 ) (see above, Figure a). Moreover, we also mutated charged amino acids localizing to the putative dimerization interface formed by the extended α5‐helix (D 172 ) or the putative functionally important site (D 302 /E 303 ) (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, mass spectrometry analysis revealed that upon acetyl phosphate treatment the LqsR G135V mutant protein was only inefficiently phosphorylated, while unexpectedly, LqsR A110V/Q136Y was still phosphorylated (Figure ). For the response regulator CheY an effect on receiver domain phosphorylation kinetics was reported for the ‘position T + 1’ (Immormino et al, ) as well as for the ‘positions D + 2/T + 2’ (Page et al, ; Thomas et al, ).…”
Section: Discussionmentioning
confidence: 98%